Lukiškių aikštė – socialinio užsakymo evoliucija. Paminklas laisvės kovų dalyviams ar simbolis „laisvė“? - Vyšniūnas, Algis (Journal of Architecture and Urbanism, 2008)
Lukiškės square – evolution of a social order. A monument to fighters for freedom or a symbol “freedom“? This paper is about public spirit, national monuments and a sign system in Lukiškės Square in Vilnius. Such a system is a part of national Policy, therefore, one should keep distinct the pure artistical and national identity ideas. Nowadays a sense of national pride is very important and at the same time a real problem in Lithuania. A nation always has an essential place, a system of symbols or an extraordinary monument. Lithuania is only getting ready to consider the issue of monuments and signs in all its aspects. That is why, according to the rules of Lukiškės Square architectural competition, it is demanded to solve this problem. A representative function is required. „The memory of an unknown partisan and fighter for Lithuania’s freedom will be memorialized“ a slogan incused on a stone panel proclaims in Lukiškės Square. But there are still no results. The conception of public space is unidentified, so an urban space and ordinary functional aspects are always muddled up. West European public space practice indicates that Renaissance squares are the most popular, multifunctional public spaces. The space system and nominal space hierarchy are very complicated and indefinite, therefore, the final result is under diferent interpretations. Memorialization of dedication to fighters for Lithuania’s freedom is of great importance, but practical square formation aspects, such as parking, fountain construction, etc., are also important. The Lithuanian Parliament adopted a resolution on Lukiškės Square functions (11 Feb. 1999), but pursuancee belongs to the Municipality. That is a mistake and a real problem because the Municipality’s activities are not transparent. Such problems must be solved by a Steering Committee which must be formed. Otherwise a qualitative result is impossible. In 2008 Lukiškės Square architectural competition was proclaimed. The format of the main task is double – urban and artistical aspects are declared. The result of this competition is an abstract artistical accent, but not a real representative memorial. The purpose of this work is to reveal the formation process of Lukiškės Square as the main square of Lithuania. The basic principles of the Square formation and those of erecting a monument to the Lithuanian freedom fighters are presented. Article in Lithuanian. Santrauka. 2008 m. paskelbtas Lukiškių aikštės sutvarkymo ir simbolio „Laisvė“ projekto sukūrimo konkursas. Vertinimo komisija išrinko 7 geriausius konkursinius projektus. Šie rezultatai sukėlė daug diskusijų, nes neaišku, ar tikrai pasiektas pagrindinis konkurso tikslas – įprasminti Laisvės kovas ir pagerbti tų kovų dalyvių atminimą? Nors yra labai konkretus LR Seimo nutarimas „Dėl Lukiškių aikštės funkcijų“, vis tiek lieka neaiškus Lukiškių aikštės statusas: ar ji yra valstybinio rango aikštė, ar paprasta vieša savivaldybės erdvė? Kai neaiškus aikštės statusas, neaiškus ir tikslo realizavimo mechanizmas bei priemonės. Straispnyje apžvelgiami pagrindiniai Lukiškių aikštės urbanistinės plėtros etapai, įvertinant ne tik realizacijas, bet ir visas idėjas, profesines koncepcijas. Pagrindinis straipsnio tikslas – atskleisti Lukiškių aikštės formavimo mechanizmus, bet ne komentuoti atskirus meninius pasiūlymus. Straipsnyje nekomentuojami atskirų suinteresuotų socialinių ir politinių grupių pareiškimai, taip pat tariamai moksliniai pranešimai viešųjų ryšių renginiuose ir akcijose. Taip pat nediskutuojama apie grynojo meno paskirtį ir santykį su mokslu ir politika. Išvadose pateikiami Lukiškių aikštės urbanistinio formavimo ir paminklo Laisvės kovotojams statymo principai. Reikšminiai žodžiai: nacionalinė savigarba, architektūrinis konkursas, viešieji ryšiai, meninis akcentas, simbolis, paminklas, aikštė, skveras, urbanistinė struktūra, paminklas Laisvės kovų dalyviams. First Published Online: 22 May 2013